The Dynamics of Radio-Cesium in Soils and Mechanism of Cesium Uptake Into Higher Plants: Newly Elucidated Mechanism of Cesium Uptake Into Rice Plants - Rai, Hiroki; Kawabata, Miku (Frontiers in Plant Science, 2020)
Soil radio-cesium (Cs) contamination caused by nuclear accidents is a major public concern. In this review, we presented the behavior of radio-Cs in soils, the relationship between Cs+ and potassium (K) ion uptake from soils, and the Cs+ uptake model proposed previously. Finally, we introduced the newly elucidated mechanism of Cs+ uptake in rice plants and compared it with the previously proposed Cs+ uptake model. Cs is a trace element in soil. It is toxic to plants when absorbed at high concentrations, although this rarely occurs under normal environmental conditions. Nevertheless, radio-Cs released during nuclear weapon tests or nuclear power plant accidents is absorbed by plants, thus entering the food chain. As Cs+ strongly binds to the frayed edge sites of illitic clays in soil, it is hardly moved by the infiltration of rainwater. However, plants have a strong ability for inorganic ions uptake, causing re-diffusion of radio-Cs+ into ecosystems and radioactive contamination of food. It is hypothesized that Cs+ is absorbed by plants through the same mechanism implemented in K+ uptake. However, the dynamics of the two elements do not always coincide in their transition from soil to plants and inside the plants. A previously proposed model of Cs uptake by higher plants stated that Cs+ is absorbed through high affinity potassium (HAK) family of transporters and voltage-insensitive cation (VIC) channels. A knockout line of a HAK transporter gene (oshak1) in rice revealed that the high affinity potassium transporter OsHAK1 is the main route of Cs+ influx into rice plants, especially in low-potassium conditions. The K+ uptake rates did not differ greatly between the oshak1 and wildtype. On the surface of rice roots, potassium-transport systems other than OsHAK1 make little or no contribution to Cs+ uptake. It is almost certain that OsAKT1 does not mediate the Cs uptake. Under normal soil conditions, 80–90% of Cs uptake into the roots is mediated by OsHAK1 and the rest by VIC channels. Except for the difference between the contribution ratio of HAK and VIC channels in Cs uptake, these results are consistent with the conventional model.